Radikalisme, Deradikalisme Dalam Kacamata Pendidikan Agama Islam - Afriandi, Afriandi; firqatun, didi; Sunalti, Esi; Ulum, Fathul (STAI YAPIS Takalar, 2025)
Indonesia is a country rich in cultural, ethnic, religious, and ethnic diversity, making it a multicultural nation. However, this diversity faces serious challenges in the form of increasing radicalism that has the potential to threaten the unity and harmony of society. Radicalism in the name of religion, especially Islam, has given rise to various acts of violence and terrorism that have disturbed society. Education, especially Islamic Religious Education, plays an important role in instilling the values ??of moderation, tolerance, and pluralism so that the younger generation does not fall into extreme ideologies. This study uses a quantitative deductive method by collecting data from various journals and research literature related to radicalism and deradicalization in Islamic education environments. This study identifies various factors that cause radicalism, such as socio-economic injustice, extreme interpretations of religion, and global influences. The role of educational institutions, including Islamic boarding schools, is very important in implementing deradicalization programs by strengthening the understanding of moderate Islam and integrating the values ??of Pancasila and multicultural education into the curriculum. Deradicalization efforts are carried out through intracurricular and extracurricular activities that instill attitudes of tolerance, moderation, and respect for diversity. Collaboration between the government, educational institutions, families, and communities is very important in strengthening deradicalization and maintaining the integrity of the Unitary State of the Republic of Indonesia (NKRI).